Pengaruh antara Intensitas Penggunaan Media Sosial terhadap Kecemasan Sosial Remaja SMA “X” di Sidoarjo - Tony Nuswantoro Azam Yosin; Zaki Nur Fahmawati (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of social media usage intensity on social anxiety in adolescents at Senior High School X in Sidoarjo. The study used a quantitative approach with a correlational method, involving 279 students as a sample selected using a probability sampling technique with stratified sampling. Data collection was carried out through a Likert scale questionnaire that measured the intensity of social media usage and social anxiety, with reliability test results showing very strong Cronbach alpha values ​​for both variables. Data analysis using simple linear regression showed that the intensity of social media usage significantly influenced social anxiety with a significance value of 0.032 (p < 0.05) and a coefficient of determination of 55.9%, which means that the intensity of social media usage contributes significantly to the level of social anxiety in adolescents. The results also showed that the majority of students were in the category of moderate intensity of social media usage and social anxiety. This finding indicates that the higher the intensity of social media usage, the higher the social anxiety experienced by adolescents, so that wise management of social media usage is needed to minimize the negative impact on adolescent mental health.